The Charismatic Religious Sheikh Maulana Ibrahim Al-Khalidi’s Leadership from Max Weber's Perspective - Siska Endang Susanti (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
This research discusses the charismatic religious leadership of Sheikh Maulana Ibrahim Al-Khalidi Kumpulan from Max Weber’s perspective. The aim of this research is basically to find out what the forms of charismatic religious leadership of Sheikh Maulana Ibrahim Al-Khalidi Kumpulan are, and to find out Max Weber’s views on the charismatic religious leadership of Sheikh Maulana Ibrahim Al-Khalidi Kumpulan. The research method used in this research is a qualitative descriptive method. Data collection was carried out by interviews, observation and documentation. The research location is Jorong Koto Tuo Nagari Koto Kaciak. The informants in this research were six people consisting of descendants of Sheikh Maulana Ibrahim Al Khalidi Kumpulan, cemetery managers, and youth leaders. The research results show that charismatic religious leadership is characterized by how a leader's charisma influences his followers. In influencing followers, leaders are able to guide them to live a moral life in accordance with Islamic beliefs. Furthermore, a religious leader possesses a personal connection, which refers to the extent to which the leader connects with his followers.